Results of Split Thickness Skin Grafts after Scalp Rotation Flap Surgeries: A Cross-Sectional Study - Hassan Kashif, Shazia Manzoor, Mahak Ali, Aiman Naseem, Saba Kiran, Syed Aaqil Shah (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess outcome of Split thickness skin grafts after scalp rotation flap Surgeries. Study design: A cross-sectional study Place and Duration:This study was conducted at Patel Hospital Karachi Pakistan fromFebruary 2021 to February 2022. Methodology: This study aimed to assess clinical features, patient demographics, results, and long-term follow-up to identify its effectiveness in other procedures. A total of 15 individuals were incorporated in the present study, those who had combination scalp reconstruction and cranioplasty with anSplit thickness skin graftsfor local donor site covering. Before surgery, five patients (33.3 %) were classified as having "high complexity" scalp abnormalities. Six (40 %) patients were large, while 9 (60 %) were medium size. The remaining grafts were inset over bare Calvarial bone, while 10 (66.7%) were inset over vascularized muscle or pericranium. Results: The authors observed that all Split thickness skin grafts in this group were successful 93.3 % of the time (14/15). Due to poor take, grafts failed were observed in 1 patient. Because of the excellent success rate in this series, no patient risk factors were observed to be associated with transplant failure. Furthermore, whether the graft resided over bone or vascularized muscle/pericranium did not affect the success rate. Conclusion: Cranioplasty poses a challenge to surgeons. Split thickness skin Grafting has shown more promising results with simple techniques than other multifaceted reconstructive methods. Keywords:Calvarial bone, Cranioplasty, Split thickness skin grafts ,Percranium, Skin grafts